WOMEN’S ATTITUDE TOWARD CERVICAL CANCER EARLY DETECTION USING THE VIA TEST METHOD - Riska Audina; Ermiati Ermiati; Sukmawati Sukmawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
The incidence of cervical cancer in Indonesia is still high, cervical cancer is detectable, the earlier in detecting cancer, the more potential to treat. The Visual inspection of the cervix with the Acetic acid (VIA) test is an early detection method to check the abnormal conditions of cervical. This test is simple, easy, accurate, effective and inexpensive. The purpose of this study was to determine the attitudes of women about early detection of cervical cancer using the VIA test method. This quantitative descriptive study involved 339 adult Women aged 30-50 years. The respondents were chosen using a purposive sampling technique. Data were collected using instruments of the attitudes of women about early detection of cervical cancer with the VIA Test. The study was conducted from May-July 2019. The results showed that most respondents had negative attitudes (56.3%). Based on the sub-variables, the most negative attitudes identified from the cognitive components (52.2%), negative affective components (60.2%) and negative conative components (73.8%). In conclusion, most women had a negative attitude towards the early detection of cervical cancer with the VIA test. It is expected that women would seek information about the importance of the VIA Test, proactively. Health workers should improve health education activities for women and families about the importance of cancer screening. Keywords: Attitude, early detection, VIA Examination, WUS.Hasil penelitian menunjukan sebagian besar responden memiliki sikap negatif sebanyak (56,3%). Berdasarkan sub variabel sikap komponen kognitif sebagian besar negatif (52,2%), sikap komponen afektif sebagian besar negatif (60,2%) dan pada sikap komponen konatif sebagian besar negatif (73,8%). Simpulan didapatkan bahwa sebagian besar WUS bersikap negatif terhadap deteksi dini kanker serviks dengan IVA. Saran bagi tenaga kesehatan diharapkan meningkatkan penyuluhan kesehatan kepada WUS tentang pentingnya pemeriksaan IVA dengan harapan terjadi perubahan sikap yang positif.Kata Kunci : Deteksi Dini, Pemeriksaan IVA, Sikap, WUSKepustakaan : 2004-2019